دراسة نسبة نجاح تطعيم صنفي الكمثرى "Cocia" و "Williams" وصنف السفرجل "الصيداوي" على أصل الكمثرى السورية Pyrus syriaca Boiss. وتطور الغراس الناتجة. - مخول, جرجس; العيان, بديعة (Latakia University Journal -Biological Sciences Series, 2014)
نفذ هذا البحث في المشتل التابع لجامعة تشرين وفي مشتل الساحل التابع لمديرية الزراعة باللاذقية. أظهرت النتائج تفوق صنف الكمثرى "Cocia" المطعم على أصل الكمثرى السورية معنوياً على صنف الكمثرى "Williams" وصنف السفرجل "صيداوي" المطعمين على الأصل نفسه، حيث بلغت نسبة نجاح التطعيم للأصناف الثلاثة في العام الأول (100% ، 90% و 66.67%) على التوالي . وفي العام التالي (93.33%، 76.67% و 53.33%) على التوالي. و أشارت النتائج إلى وجود درجة توافق جيدة بين الصنف "كوشي" والأصل المستخدم مقارنة بالصنفين الآخرين. كما بينت نتائج التحليل الإحصائي تفوق الصنف "كوشي" على الصنفين " وليامز" و "الصيداوي" من حيث الزيادة في ارتفاع المطاعيم، وتفوق الصنف "وليامز" على الصنف "الصيداوي" وهذا يؤكد بأن الصنف "كوشي" يعتبر متوسط قوة النمو عند تطعيمه على أصل الكمثرى السورية، بينما الصنف "وليامز " فيعد مقصر في قوة النمو ، والصنف "الصيداوي" مقصر جداً عند تطعيمهما على الأصل نفسه ، خاصة في السنوات الأولى من تطعيم الغراس. This research was conducted in seedling area belonging to Tishreen University and in the Coast seedling belonging to Agricultural Directorate in Lattakia. Results has shown that, the pear variety Cocia grafted on pear Syrian rootstock was significantly better than pear variety Williams and Quince variety Saidawi grafted on the same rootstock, where the percentage of grafting were 100%, 90% and 66.67% consequently, and in the next year 93.33%, 76.67% and 54.00% consequently. Results has shown a good agreement between a variety Cocia and a used rootstock in comparison with the tow other varieties. The results of analytical calculation has shown that, the variety Cocia was better than the tow other varieties Williams and Saidawi in graft-height, also, Williams variety was better than Saidawi variety, and this confirm that, the Cocia variety in medium growth when it grafted on pear Syrian rootstock, whereas, Williams variety was in poor growth and Saidawi variety was very poor in growth when they were grafted on the same rootstalk especially in the first years of grafting.